INVESTIGATION OF ZERO CARBON DIOXIDE SYNGAS-BIODIESEL BLENDS FOR DUAL FUELING OPERATION IN A CI ENGINE - MAHGOUB, BAHAADDEIN KAMAL MOHAMED (2018)
This study investigated simulated syngas produced from biomass gasification in a compression ignition (CI) engine under a dual fueling (DF) mode of operation. Syngas is an economical solution with a carbon neutral system that can be introduced into CI engines through dual fueling process in order to substitute diesel. However, syngas DF combustion is a very complicated process that consists of several combustion phases.